Age-dependent associations between telomere length and environmental conditions in roe deer. (27th September 2017) - Wilbourn, Rachael V.; Froy, Hannah; McManus, Marie-Christina; Cheynel, Louise; Gaillard, Jean-Michel; Gilot-Fromont, Emmanuelle; Regis, Corinne; Rey, Benjamin; Pellerin, Maryline; Lemaître, Jean-François; Nussey, Daniel H.
Abstract : Telomere length (TL) represents a promising biomarker of overall physiological state and of past environmental experiences, which could help us understand the drivers of life-history variation in natural populations. A growing number of studies in birds suggest that environmental stress or poor environmental conditions are associated with shortened TL, but studies of such relationships in wild mammals are lacking. Here, we compare leucocyte TL from cross-sectional samples collected from two French populations of roe deer which experience different environmental conditions. We found that, as predicted, TL was shorter in the population experiencing poor environmental conditions but that this difference was only significant in older individuals and was independent of sex and body mass. Unexpectedly, the difference was underpinned by a significant increase in TL with age in the population experiencing good environmental conditions, while there was no detectable relationship with age in poor conditions. These results demonstrate both the environmental sensitivity and complexity of telomere dynamics in natural mammal populations, and highlight the importance of longitudinal data to disentangle the within- and among-individual processes that generate them.